Environmental Quality Development Strategy in Central Government Areas: Case Study of Dompak Island, Riau Islands Province - Roby Cahayadi; Yuanita FD Sidabutar; Cevy Amelia; Isramilda (Graduate Program Magister Manajemen Pendidikan, 2024)
Environmental quality refers to the state or condition of the environment in a particular area, taking into consideration various factors that affect the well-being of living organisms, including humans. It encompasses the health and sustainability of ecosystems, air, water, soil, and other natural resources. The interpretation of environmental quality as providing optimal carrying capacity for human survival implies that the environment should meet certain criteria to support human life and well-being. This research aims to find out how to apply and development strategy in providing regional facilities and infrastructure to optimize environmental quality on Dompak Island as the Central Government Area of the Riau Islands Province. This research uses a qualitative method with a descriptive approach through SWOT analysis. The research results found that the strategy for providing facilities and infrastructure to improve environmental quality on Dompak Island is by developing a drinking water supply system (SPAM), increasing drainage capacity, providing street lighting infrastructure, providing green open space, maintaining existing physical infrastructure, utilizing empty land. for the construction of parking lots, collaboration with other parties and strengthening regional management institutions. The novelty of this research involves various infrastructure components, effective use of resources, multi-party collaboration, institutional strengthening, and strategies based on SWOT analysis to achieve the goal of improving sustainable environmental quality on Dompak Island.